Investigating the Normal Management Regimens of Working Equids and Identifying Barriers to the Recognition and Treatment of Colic by Owners in Morocco. (September 2015) - Kalamanova, A.; Stringer, A.P.; Freeman, S.L.; Burford, J.H.
Abstract : Reasons for performing study: Colic is a common reason for owners to seek veterinary treatment for their working equids in Morocco. There is no information available regarding cultural, religious or educational barriers to obtaining treatment or about the typical workload of these animals which may predispose them to colic. Objectives: To characterise the typical workload and feeding regimens of working equids in Morocco; to characterise the ability of owners to recognise the clinical signs and causes of colic; and to identify specific barriers to the veterinary treatment of colic. Study design: Questionnaire‐based survey. Methods: A standardised, structured questionnaire was administered, with the assistance of an Arabic speaking interpreter, to the owners of working equids presenting their animals to 2 centres run by SPANA (The Society for the Protection of Animals Abroad). Participation was voluntary and informed consent was obtained prior to the interview. Results: All of the 102 participants that completed questionnaire were male. Ninety‐eight owners used their animals for pulling carts, with 12% of animals working 7 days per week. 14% of animals were offered water by their owner once per day and 2% every other day. 25% of animals were loose and allowed free to feed unsupervised when not working. 29% of owners were not able to name any cause of colic and 25% did not recognise any clinical signs; only 12% associated colic with gastrointestinal pain. 83% of owners would not seek veterinary treatment due to financial constraints if free treatment at SPANA centres were not available. Conclusions: Colic remains a common problem amongst working equids in Morocco. Improved knowledge of management factors associated with colic and how to recognise abdominal pain may reduce the incidence of colic and improve prognosis. The findings presented can be used to inform and develop owner education programmes. Ethical animal research: The study was reviewed and approved by the Ethics Committee, School of Veterinary Medicine and Science, University of Nottingham. Informed consent for participation in the study was obtained from all owners and was delivered in the native language. No details identifying the owner were recorded.Source of funding: None.Competing interests: None declared.